The Impact of Faith and Experience on the Development of Coaching Philosophies - Douglas Hochstetler (Movement and Being: The Journal of the Christian Society for Kinesiology, Leisure and Sports Studies, 2012)
The purpose of this paper is to address coaching philosophies in the context of experience and faith. In particular, how do coaches at Christian colleges develop their ideas and beliefs about coaching which guide their actions and behaviors? To what extent does faith impact these philosophical commitments? What is this process of decision-making and growth like? Does this development process occur intuitively, through rational discourse and planning, or perhaps through some sort of symbiotic process? This paper is both descriptive and normative, both reflective of the experiential process in developing one’s coaching philosophy as well as prescribing effective ways to integrate faith, experience, and coaching ideals and practices. Establishing a coaching philosophy is indeed a developmental process. For the attentive coach, coaching guidelines and principles change over time. Second, a coaching philosophy is developed through experience more so than being derived from abstract principles. While individuals may promote concepts like fairness or compassion, these principles are fleshed out and modified through relationships. Third, a coaching philosophy informed and constructed by faith, when properly and consistently applied, can play an important part in this process. Coaches may draw from their own faith experiences in ways that positively impact the team climate.
Keywords: Sport; faith-based; leisure; spirituality; coaching